Heidelberg Aesthetics: Review of: Georg Lukács (2022): Estética de Heidelberg (1916-1918), Zaragoza: Prensas de la Universidad de Zaragoza. - Blanco, Carlos (Analysis. Journal of Philosophical Research, 2023)
Review of: Georg Lukács (2022): Estética de Heidelberg (1916-1918), Zaragoza: Prensas de la Universidad de Zaragoza, 338 pp.